Analisis Beban Kerja Fisik Dan Mental Bagian Produksi Dengan Menggunakan Metode Cardiovascular Load (CVL) Dan Bourdon Wiersma Di PT. Romi Violeta - Sarah Aliyah Sabhirah; Rusindiyanto Rusindiyanto (Pusat Riset dan Inovasi Nasional, 2023)
A manufacturing company engaged in the furniture industry, specializing in wood, rattan and glass products. Most of the production orders were related to table products, stands and chests, with a total of 15,224 orders for other products. Based on results of direct observation at PT. Romi Violeta from the production process department says that due to the limited working hours, especially as the production orders for tables, shelves, etc. increase every month, the physical and mental strain employees take to meet their production targets. I often complain about. For commodity products. The purpose of the research is to find cases of high physical and mental stress at manufacturing sites with high stress standards such as tables, shelves, and chests of drawers, and to provide suggestions for improving the reduction of physical and mental stress. . Based on an analysis of the results, the mean cardiovascular load (CVL) percentage was found to be 43.902%, indicating that the assessment needs improvement, and the Bourdon Vielsma test speed result was 12.593 seconds with a score of 7. , a body weight score (WS) of 11.5 is included in the adequate group (C). Accuracy is 3.26, score is 8, fair group (CB) weighted score (WS) is 12, constant is 8.185 seconds, score is 5.5, score is . 8 are in the suspicious (R) group.